Integrating models for calculating component sustainability metrics - Kirkwood, Leigh; Abu-Monshar, Anees; Norman, Beth; Crook, Robert; Barlow, Ed; Hayes, Cai; Rybicka, Justyna (Cranfield University, 2024)
This paper reports on the development of models for calculating sustainability metrics at a per part level, developed for the LEAD factory project. While many organisations collect site level data for sustainability, there is a notable lack of support to calculate at a per part level. This scope difference requires different methods, but part level information can aid organisations in making production changes to achieve sustainability KPI’s. A cradle-to-gate approach was used that links raw-material, the transportation of materials and details on the production processes. To achieve this, a toolset of different models was designed and built to address key activities in the value-chain, to both support potentially independent analysis of just that value-chain link or the more complete cradle-to-gate analysis. Integration of model outputs and planning of information flow within the toolset is the primary focus of this paper. This is part 1 of a 2 part paper: this paper focuses on how the models were integrated and the design of the wider toolset. Part 2 focuses on the benchmarking using the model-set and comparing the “JENI” system developed as part of the LEAD factory project.
Keywords: Sustainable manufacturing; supply chain; carbon-dioxide equivalent